AVALIAÇÃO DO IMPACTO DO LODO DE ESGOTO NA MICROBIOTA DO SOLO UTILIZANDO O GENE 16S rRNA - Pedrinho, E.a.n. [UNESP]; Lemos, E.g.m. [UNESP]; Pereira, R.m. [UNESP]; Scaquitto, D.c. [UNESP]; Silveira, É.l. Da [UNESP]; Val-moraes, S.p. [UNESP]; Alves, L.m.c. [UNESP]; Wickert, E. [UNESP]; Valarini, M.j. (Instituto Biológico, 2021)
The objective of this work was to evaluate and compare the microbial diversity of a soil treated with sewage sludge (BAR 1N) with the same soil without treatment (control). The use of industrial and domestic sewer sludge as organic fertilizer in agricultural soils is currently considered a promising alternative for the final destination of these residues. Molecular studies using the analysis of the gene 16S rRNA provide relevant information in regard to studies of microbial ecology, since it is believed that only 10% of these microorganisms can be cultivated. The sequences were submitted to analysis of nucleotide similarity, based on data in GenBank, in order to be identified and classified. Following phylogram analysis, a high number of nonidentified microorganisms were observed in the investigated soils. The results demonstrated that the outstanding bacterial phyla were Acidobacteria and Proteobacteria. Phylogenetic analyses revealed differences in both soils, based on the bacterial diversity index, showing that the test soil had more diversity when compared to the BAR 1N soil.

Este trabalho teve por objetivo estimar e comparar a diversidade microbiana de um solo tratado com lodo de esgoto (BAR 1N) com o mesmo solo sem tratamento (controle). A utilização do lodo de esgoto de origem industrial ou domiciliar em solos agrícolas como adubo orgânico é considerado, atualmente, uma alternativa promissora para disposição final deste resíduo. Estudos moleculares que utilizam a análise do gene 16S rRNA permitem a obtenção de informações relevantes acerca da ecologia microbiana, pois acredita-se que apenas 10% desses microorganismos podem ser cultivados. O DNA genômico dos micro-organismos presentes em ambos os solos foi extraído, clonado e, após amplificação por PCR, foi feito o sequenciamento do gene 16S rRNA. As sequências obtidas foram submetidas à análise de similaridade de nucleotídeos com o banco de dados GenBank para que pudessem ser identificadas e classificadas. Após a análise dos filogramas observou-se um número elevado de micro-organismos não identificados nos solos analisados. Os resultados demonstraram que os filos bacterianos que se destacaram foram Acidobacteria e Proteobacteria. Análises filogenéticas revelaram diferenças entre os solos, mostrando por meio de índice de diversidade bacteriana que o solo controle apresentou maior diversidade quando comparado ao solo BAR 1N. O filo Nitrospira revelou-se significativamente afetado pela aplicação do lodo de esgoto.
EVALUATION OF THE IMPACT OF SEWAGE SLUDGE ON SOIL MICROBES USING THE 16S RRNA GENE
Keywords: Biossolid; microbial ecology; metagenomic; Biossólido; ecologia microbiana; metagenoma